Reticulate acropigmentation of Dohi: A rare case (Indian Journal of Case Reports, 2025)
Reticulate acropigmentation of Dohi (RAD) is a rare genodermatosis characterized by reticulated hyperpigmented and hypopigmented macules, primarily involving the acral areas. Although typically inherited as an autosomal dominant trait, autosomal recessive inheritance has also been reported. We present a rare case of a 36-year-old female with widespread hyperpigmented patches across her body, with disease onset at 16 years of age. Histopathological examination of a skin biopsy revealed basal melanosis, increased melanocytes throughout the epidermis, and dermal melanophages, supporting the diagnosis of RAD. Dermoscopic findings correlate well with histopathological changes. No effective treatment exists, with cosmetic camouflage being the most practical approach. This case is reported due to the rare, sporadic occurrence of RAD without a family history and extensive body involvement.